Retaining Talent: Quality Rating Systems as a Workforce Stabilization Strategy in Post-Katrina New Orleans. - Gibbons, Eugenia T.; Husak, Maggie.; Smith, Sherise S. (Tufts University. Tisch Library., 2018)
2009 M.A. in Urban and Environmental Policy and Planning Field Project. Client: United Way for the Greater New Orleans Area, Success By 6.